2000
DOI: 10.1523/jneurosci.20-05-01837.2000
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin-Driven Long-Range Inhibitory Connections in the Cerebellar Cortex

Abstract: Disturbances of the serotoninergic neuromodulation in the cerebellar cortex have been involved in several types of ataxia, but the physiological action of serotonin in this structure remains poorly understood. We report that in slices of the rat cerebellar vermis, serotonin triggers the firing of an inhibitory interneuron presynaptic to Golgi cells. The Lugaro cell, a neglected interneuronal type, satisfies the expected criteria for this input, whereas basket cells, stellate cells, or Golgi cells do not. Lugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
144
5

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(163 citation statements)
references
References 49 publications
11
144
5
Order By: Relevance
“…They are found in all parts of the cerebellar cortex, where they are located at the border between the Purkinje cell layer and the upper part of the granule cell layer. Initial numerical estimates had put the Purkinje cell/ Lugaro cell ratio at about 15:1 in the rat (Dieudonne and Dumoulin 2000) and 30:1 in the cat (Sahin and HockWeld 1990). More recently, a detailed neurochemical analysis of large granule cell layer interneurons indicated that in the mouse, Lugaro cells account for about 1/3 of all inhibitory granule cell layer interneurons, and thus are more numerous than initially estimated (Simat et al 2007).…”
Section: Large Inhibitory Interneurons Of the Granule Cell Layermentioning
confidence: 96%
See 2 more Smart Citations
“…They are found in all parts of the cerebellar cortex, where they are located at the border between the Purkinje cell layer and the upper part of the granule cell layer. Initial numerical estimates had put the Purkinje cell/ Lugaro cell ratio at about 15:1 in the rat (Dieudonne and Dumoulin 2000) and 30:1 in the cat (Sahin and HockWeld 1990). More recently, a detailed neurochemical analysis of large granule cell layer interneurons indicated that in the mouse, Lugaro cells account for about 1/3 of all inhibitory granule cell layer interneurons, and thus are more numerous than initially estimated (Simat et al 2007).…”
Section: Large Inhibitory Interneurons Of the Granule Cell Layermentioning
confidence: 96%
“…These dendrites are of rather variable length, measuring, in the rat, from some 100 to 700 m (Laine and Axelrad 1996). Lugaro cells are currently viewed as the primary target of serotoninergic input into the cerebellar cortex (Dieudonne and Dumoulin 2000). They are also innervated by recurrent Purkinje cell axon collaterals (Palay and Chan-Palay 1974), and basket cells (Fox et al 1967).…”
Section: Large Inhibitory Interneurons Of the Granule Cell Layermentioning
confidence: 99%
See 1 more Smart Citation
“…The precisely timed response components were generated in the model with trigeminal MF and PF excitation alone, i.e. without a need for other, non-modelled synaptic inputs to Golgi cells originating from Lugaro cells (Dieudonne ¤ and Dumoulin, 2000), stellate cells, climbing ¢bres, the pontine nuclei (Leergaard et al, 2000) or the lateral reticular nucleus.…”
Section: Sources and Timing Of Synaptic Inputs To Golgi Cellsmentioning
confidence: 99%
“…Although other pathways and mechanisms cannot be excluded to have contributed to our experimental observations, it is unclear how they would generate delays with a spatially anisotropic pattern. For example, the inhibitory Lugaro cells were proposed to synchronise Golgi cells (Dieudonne ¤ and Dumoulin, 2000). It would indeed be di⁄cult to distinguish, from the CCH, common inhibition from common excitation as the cause of synchrony .…”
Section: Sources and Timing Of Synaptic Inputs To Golgi Cellsmentioning
confidence: 99%